The quiet American - Horberg, William; Ahrenberg, Staffan; Hampton, Christopher, 1946-; Schenkkan, Robert, 1953-; Noyce, Phillip; Caine, Michael; Fraser, Brendan, 1968-; Yen, Do Thi Hai.; Ma, Tzi.; Stanton, Robert; Osborne, Holmes, 1952-; Hoa, Pham Thi Mai.; et al. ([United States] : Miramax Home Entertainment ; Burbank, Calif. : Distributed by Buena Vista Home Entertainment, 2003)
A story that led to the events of the United States military involvement in Vietnam. Here, a love triangle between a British journalist, his mistress, and a mysterious CIA operative evolves into a much greater mystery that eventually leads to murder and deception.
English track: Dolby digital 5.1.
Special features: anatomy of a scene; director's commentary; behind-the-scenes featurette.
Originally released as a motion picture in 2002.
Based on the novel by Graham Greene.
Director of photography, Christopher Doyle ; editor, John Scott; original music composer, Craig Armstrong ; costume designer, Norma Moriceau ; production designer, Roger Ford.
Michael Caine, Brendan Fraser, Do Thi Hai Yen, Tzi Ma, Robert Stanton, Holmes Osborne, Pham Thi Mai Hoa, Quang Hai, Rade Sherbedgia.
Keywords: Triangles (Interpersonal relations) -- Drama; Vietnam -- History -- 1945-1975 -- Drama; Feature films; Films for the hearing impaired